Neil Patrick Harris [compact disc, unabridged] : choose your own autobiography - Harris, Neil Patrick, 1973- (Books on Tape : Random House Audio, 2014)
This hilarious book has been adapted especially for the audiobook edition so listeners hear all of the same fun and humor from the printed version and don't have to make any decisions or jump around, just kick back, relax and listen. Plus, it features exclusive bonus audio of young Neil delivering an adorable speech.